Understanding the associations between information sources, sociodemographics, and views on public health measures: evidence from the COVID-19 pandemic in Austria - Peter Gamillscheg; Susanne Mayer; Monika Pietrzak-Franger; Carina Hilmar; Alina Lange; Judit Simon; Agata Łaszewska (BMC, 2024)
Abstract Background Throughout the COVID-19 pandemic, it was a key priority for governments globally to ensure agreement with, and subsequently adherence to, imposed public health measures, specifically non-pharmaceutical interventions (NPIs). Prior research in this regard highlighted the role of COVID-19 information sources as well as sociodemographic and other personal characteristics, however, there is only limited evidence including both. To bridge this gap, this study investigated the associations of COVID-19 information sources such as social media and participant characteristics with agreement with and adherence to NPIs during the first lockdown in Austria. Methods An online survey was conducted in May 2020 among adult Austrian residents asking about their experiences during the first lockdown. Collected data included sociodemographic characteristics, main COVID-19-related information sources, agreement with/adherence to three NPIs (no physical contact to family members not living in the same household, leisurely walks restricted to members of the same household, mandatory face masks) and information about perceived social support using the Multidimensional Scale of Perceived Social Support (MSPSS), anxiety/depression levels using the Hospital Anxiety and Depression Scale (HADS), whether participants felt well advised by the government, and whether participants perceived the pandemic to threaten their income. Ordered and multinomial logistic regression models were employed to achieve the research aims. Results The cross-sectional sample consisted of 559 Austrian residents. Using social media as main COVID-19 information source was consistently associated with lower agreement with NPIs. A positive association with agreement with measures was found for higher educational backgrounds and higher anxiety levels. By contrast, higher levels of depression, not feeling well advised by the government, and perceiving the pandemic as an economic threat were negatively associated with agreement with measures. Moreover, the use of social media as main COVID-19 information source and not feeling well advised by the government were associated with lower adherence to NPIs. By contrast, higher levels of education were associated with higher adherence. Conclusions This comprehensive analysis emphasizes the associations of COVID-19 information sources as well as sociodemographic and other participant characteristics with agreement with and adherence to NPIs, bearing important implications for future public health crisis communication strategies.